Vitamin E and N-Acetylcysteine as Antioxidant Adjuvant Therapy in Children with Acute Lymphoblastic Leukemia - Youssef Al-Tonbary; Mohammad Al-Haggar; Rasha EL-Ashry; Sahar EL-Dakroory; Hanan Azzam; Ashraf Fouda (Advances in Hematology)
Although cancer therapies have experienced great success nowadays, yet the associated toxic response and free radicals formation have resulted in significant number of treatment-induced deaths rather than disease-induced fatalities. Complications of chemotherapy have forced physicians to study antioxidant use as adjunctive treatment in cancer. This study aimed to evaluate the antioxidant role of vitamin E and N-acetyl cysteine (NAC) in overcoming treatment-induced toxicity in acute lymphoblastic leukaemia (ALL) during the intensive period of chemo-/radiotherapy, almost the first two months of treatment. Forty children newly diagnosed with ALL were enrolled in this study. Twenty children (group I) have taken vitamin E and NAC supplementations with chemotherapy and the other twenty children (group II) have not taken any adjuvant antioxidant therapy. They were evaluated clinically for the occurrence of complications and by the laboratory parameters (blood levels of glutathione peroxidase (Glu.PX) antioxidant enzyme, malondialdehyde (MDA), tumor necrosis factor-𝛼 (TNF-𝛼), liver enzymes, and bone marrow picture). Results revealed reduced chemotherapy and radiotherapy toxicity as evidenced by decreasing level of MDA, increasing level of Glu.Px and decreased occurrence of toxic hepatitis, haematological complications, and need for blood and platelet transfusions in group I compared to group II. We can conclude that vitamin E and NAC have been shown to be effective as antioxidant adjuvant therapy in children with ALL to reduce chemo-/radiotherapy-related toxicities during the initial period of treatment.